P53 tumor suppressor is required for efficient execution of the death program following treatment with a cytotoxic limonoid obtained from Melia azedarach - Joray, Mariana Belén (2017)
This work examines the antitumor activity of an isomeric mixture (1), composed of the limonoids meliartenin and its interchangeable isomer 12-hydroxyamoorastatin. The results obtained showed that 1 displayed outstanding cytotoxic activity against CCRF-CEM, K562, A549 and HCT116 cells, with a highly selective effect on the latter, with an IC50 value of 0.2 μM. Based on this finding, HCT116 cells were selected to study the mechanism of action of 1. Cell cycle analysis revealed that 1 induced sustained arrest in the S-phase, which was followed by the triggering of apoptotic cell death and reduced clonogenic capacity. This cytotoxicity was seen to be preceded by the upregulation of the tumor suppressor p53 and its target effector p21. In addition, it was found that p53 expression was required for efficient cell death induction, and thus that the toxicity of 1 relies mainly on p53-dependent mechanisms. Taken together, these findings position 1 as a potent antitumor agent, with potential for the development of novel chemotherapeutic drugs based on the induction of S-phase arrest.